Anthropometric Variables and Nutritional Status of Adolescent School Girls in a Food Insecure Rural Area of Bangladesh. - Mohammad Azizur Rahman; Reza Ul Karim (Universiti Kebangsaan Malaysia, 2013)
This study estimated the anthropometric variables and nutritional status of rural adolescent school girls of food insecure Bera subdistrict of Pabna district in Bangladesh.